Is central bank currency fundamental to the monetary system? - Hanna Armelius; Carl Andreas Claussen; Scott Hendry (Bank of Canada, 2020)
In this paper, we discuss whether the ability of individuals to convert commercial bank money (i.e., bank deposits) into central bank money is fundamentally important for the monetary system. This is a significant question since the use of cash - the only form of central bank money that the public currently has access to - is declining rapidly in many countries. The question is highly relevant to the discussion around whether central banks need to issue a retail central bank digital currency (CBDC). We conclude that depositors' need for control could be a reason why cash or a CBDC is essential, even in countries with strong measures safeguarding commercial bank money.
Keywords: E; E4; E41; E42; E5; 330; Bank notes; Digital Currencies and fintech; Financial services; Payment clearing and settlement systems